QIYAS MAHARAH SUR'AH AL-QIRA'AH 'ALA MUSTAWA AL-KALIMAH BI AL-LUGHAH AL-'ARABIYAH LADA AL-TALAMIDZ AHADI WA TSANA'I AL-LUGHAH FI ALMANIYA - Esraa Naddaf (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2016)
The aim of the present study was to examine Arabic reading speed (at word level) for students in Germany, who acquire literacy in German primary schools and who speak Arabic as a mother tongue and German as a second language. This study is the first one in this research field. Acquiring Arabic literacy is challenging, on one hand because of Arabic diglossia and on the other hand very few German schools offer a chance to receive lessons in vernacular language. The finding showed a significant difference between the group (bilingual students who received Arabic lessons at school) and the group (bilingual students who received Arabic lessons at the mosque), indicating that students (groupone) benefit from literacy lessons at German schools. The data indicate that professional teachers and adequate textbooks are a prerequisite for teaching Arabic at mosques.DOI: 10.15408/a.v3i2.4582